Dolomite industrial by-products as active material for CO2 adsorption and catalyst for the acetone condensation - Ursueguía, David (Waste management (New York, N.Y.), 2023)
Copyright © 2023 The Author(s). Published by Elsevier Ltd.. All rights reserved.